Produção de Amônia na Fermentação in Vitro de Rações com Levedura, Uréia ou Farelo de Algodão - Sampaio, Alexandre Amstalden Moraes; De Figueiredo Vieira, Paulo [UNESP]; De Brito, Rodolfo Marques [UNESP] (My University, 2000)
The objective of this trial was to evaluate the in vitro ammonia (N-NH 3) production in fermentation of diets with different protein sources (dry yeast, urea and cottonseed meal) used for ruminants diets. The data relative to the N-NH 3 production measured in the first hour of incubation, showed differences between diets with cottonseed meal and dry yeast, compared with diets with urea, with values of 7.52; 8.66; and 29.84 mg N-NH 3/100 mL of ruminai fluid, respectively. The same pattern was observed until 12 hours of fermentation, with values of 1.05; 1.57; and 8.57 mg N-NH 3/100 mL. The analysis of data related to the 12 hourly sample of fermentation showed the trend of decreasing N-NH 3/100 mL concentration of ruminal fluid, reaching the lower values on 12 hours of fermentation.
Ammonia Production from in Vitro Fermentation of Diets with Dry Yeast, Urea or Cottonseed Meal
Keywords: Ammonia; Cottonseed meal; Dry yeast; Protein sources; Ruminal fermentation; Urea